2022
DOI: 10.1108/ecam-07-2022-0614
|View full text |Cite
|
Sign up to set email alerts
|

Organizational antecedents and multiple paths of knowledge-sharing behavior of construction project members: evidence from Chinese construction enterprises

Abstract: PurposeLack of knowledge-sharing behavior (KSB) among construction project members hinders propagation of expertise, working methods, and lessons learned within an organization, and deprives the organization of a sustainable competitive edge. The present study investigates the combined effect of organizational antecedents of construction projects on members' KSB and provides a reference for developing management initiatives to motivate KSB.Design/methodology/approachBased on organizational theory and organizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The current research expands upon previous studies by examining the mediating role of knowledge integration between sustainable leadership and sustainable project performance. Prior research has neglected to examine how sustainable leaders integrate sustainability practices with their management style (Cheng and Yin, 2022). In large-scale construction projects, success often hinges on the team's ability to integrate and absorb knowledge and tools related to sustainable development goals (SDGs).…”
Section: Discussionmentioning
confidence: 99%
“…The current research expands upon previous studies by examining the mediating role of knowledge integration between sustainable leadership and sustainable project performance. Prior research has neglected to examine how sustainable leaders integrate sustainability practices with their management style (Cheng and Yin, 2022). In large-scale construction projects, success often hinges on the team's ability to integrate and absorb knowledge and tools related to sustainable development goals (SDGs).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the inevitable unpredictability seen in project management, the need for knowledge governance is substantial. According to Cheng and Yin (2022), complicated projects are a challenging issue that generally includes inadequate pre-given knowledge. Carrillo et al.…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
“…Due to the inevitable unpredictability seen in project management, the need for knowledge governance is substantial. According to Cheng and Yin (2022), complicated projects are a challenging issue that generally includes inadequate pre-given knowledge. Carrillo et al (2013) also argue that complicated projects necessitate a project-wide technique for knowledge creation in which project team members take into mind their objectives and are informed by organizational decisions.…”
Section: Tacit Knowledge Sharing and Knowledge Governancementioning
confidence: 99%
“…A just culture encourages employees to report unfavorable events, and the workers feel threatened and fear punishment within the blame culture (Stemn et al, 2018). Cheng and Yin (2022) found that organizational culture-associated factors, such as trust, supportive climate and incentives, motivate knowledge sharing among construction workers, while Zhou et al (2022) concluded that organizational culture is not significantly associated with knowledge dissemination. The proposed influence model for LFQF is expected to be further examined in different learning contexts.…”
Section: Limitationsmentioning
confidence: 99%